Bempedoic Acid and the Prevention of Cardiovascular Disease - Keaney, John F. (The New England journal of medicine, 2023)
Bempedoic Acid and Cardiovascular DiseaseThis editorial describes the science behind a study of bempedoic acid in persons with or at increased risk for cardiovascular disease who were unable or unwilling to take high-intensity statins.